The effect of running on knee joint cartilage: A systematic review and meta-analysis. (January 2021) - Dong, Xueping; Li, Canfeng; Liu, Jiyi; Huang, Pengzhou; Jiang, Guanwei; Zhang, Mengdi; Zhang, Wentao; Zhang, Xintao
Abstract: Objective: Although running causes inevitable stress to the joints, data regarding its effect on the cartilage of the knee are conflicting. This systematic review and meta-analysis aimed to evaluate the effect of running on knee joint cartilage. Methods: PubMed, EMBASE, SportDiscus, and Cochrane Library databases were searched to identify randomized controlled trials (RCTs) and cohort studies. The outcome indicators were cartilage oligomeric matrix protein (COMP), cartilage volume and thickness, and T2. Results: A total of two RCTs and 13 cohort studies were included. There was no significant difference in cartilage volume between the running and control groups (MD,  −115.88 U/I; 95% CI,  −320.03 to 88.27; p = 0.27). However, running would decrease cartilage thickness (MD,  −0.09 mm; 95%CI,  −0.18 to −0.01; p = 0.03) and T2 (MD,  −2.78 ms; 95% CI,  −4.12 to −1.45; p < 0.001). Subgroup analysis demonstrated that COMP immediately or at 0.5 h after running was significantly increased, but there were no significant changes at 1 h or 2 h. Conclusions: Running has advantages in promoting nutrition penetrating into the cartilage as well as squeezing out the metabolic substance, such as water. Our study found that running had a short-term adverse effect on COMP and did not affect cartilage volume or thickness. Highlights: · A meta-analysis was done to evaluate the effect of running on knee cartilage. · A short-term adverse effect on COMP was caused by running. · Running has more advantages than disadvantages to knee cartilage. · Runners could follow the moderate principle and combine with rest.